Factors Affecting Employee Engagement: A Case of ABC Company, Indonesia - Angelina, Sylvia; Bernarto, Innocentius; Meilani, Yohana, F. Cahya Palupi (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
This study aims to examine factors affecting employee engagement at ABC company. This study was done in a quantitative manner. There were five variables used, including goal setting, job autonomy, strategic attention, role benefit, and employee engagement. The data was collected by using a questionnaire distributed to all 100 employees at ABC company (census). The questionnaire also covered the respondents’ profile including their gender, age, educational background, and length of work. The data was analyzed by using PLS-SEM in SmartPls program. The results conclude that goal setting, job autonomy, strategic attention, and role benefit were positively influenced employee engagement at ABC company. The contribution of this study is to give input for managerial ABC company and other oil companies in maintaining employee engagement.